The burning queen - Verma, Aparna (Verma, Aparna. Ravence trilogy, 2025)
""So what will you become, Elena? Villain, hero, or conqueror?" Ravence has fallen. Her enemies have ravaged her people. And now Elena Aadya Ravence must decide how far she will go to reap her revenge. As she is pulled into a bitter war that will decide the fate of her kingdom, a new tyrant rises to reclaim his home, and Elena finds that perhaps her hunger isn't enough. And his knows no bounds"-- Provided by publisher.